Вивчення роду Origanum L. в умовах південного берега Криму - ХЛИПЕНКО, ЛЮДМИЛА АНАТОЛІЇВНА; РАБОТЯГОВ, ВАЛЕРІЙ ДМИТРОВИЧ; ОРЕЛ, ТАЇСІЯ ІВАНІВНА (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Вивчення роду Origanum L. в умовах південного берега Криму